Analysis of Bus Passenger Demand and Supply: Case Study on Western Province, Sri Lanka (International Journal of Scientific Research and Management (IJSRM), 2021)
Buses carried about 47% of passengers crossing the Colombo Municipal Council (CMC) boundary in 2013. The Sri Lanka Transport Board (SLTB) and private bus companies operates roughly 680 intra-provincial bus routes and 400 inter-provincial bus routes in the Western Province according to the bus route information from the National Transport Commission (NTC, 2012) . The number of buses on the seven (7) major radial corridors carries more bus passengers than other roads in the Western Province. Kandy, Galle and Malabe Road corridors are the highest followed by High Level, Negombo, Horana and Low Level Road corridors. This research paper is an attempt to analyse the bus passenger demand and supply on seven major corridors connecting Western Province boundaries. The impact of the passenger demands and volumes from the seven major corridors and the traffic speed are the main outcome of this analysis. The present bus traffic information and the impact of the traffic congestion due to the high traffic flow on major corridors are discussed in the analysis. The research will also focus on alternative solutions and the importance of integrating other public transport modes to cater the demand from the major seven corridors for the better utilisation of public transport inside the Western Province boundaries.